Analisis Dampak dan Pemenuhan Hak Korban dalam Kasus Pagar Laut Ditinjau Berdasarkan Perspektif Greenvictimology - Siti Nur Cahyati; Salsa Billa; Rabi’ah Fajriah; Syifa Noer Rohmah (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The sea fence in Tangerang Regency, Banten, has become a complex issue involving violations of spatial law, environmental impacts, and the rights of coastal communities. This research analyzes the social and environmental impacts of the case and examines the protection and restoration of victims' rights based on a greenvictimology perspective. Using an empirical juridical approach, data collection was conducted through interviews with fishermen and legal aid organizations, as well as secondary data from legal literature. The results showed that sea fences disrupt fishermen's activities, damage marine ecosystems, and violate regional spatial regulations. Ecological impacts include changes in ocean currents, decreased water quality, disruption of fish migration, damage to coral reefs, and coastal abrasion. Protection and restoration of victims' rights in the Pagar Laut case to date have not been fully fulfilled and realized by the responsible parties. This can be seen from the absence of concrete policies and concrete actions in the form of providing compensation or compensation to fishermen who are directly affected by the installation of the Sea Fence which hampers their access and space for fishing activities. In addition, efforts to restore the marine environment have also not been carried out optimally, especially in terms of dismantling sea fences that have not been carried out thoroughly and assistance programs from the Ministry of Maritime Affairs and Fisheries have not been implemented.